Breaststroke kinematics - Seifert, L.; Leblanc, H.; Chollet, D.; Sander, R. H.; Persyn, U. (World book of swimming: From science to performance, 2012)
This chapter on breaststroke kinematics mostly presents the works of the Leuven Research and Evaluation Centre, under the direction of Professor Ulrik Persyn since 1970, and is dedicated to one of his pioneering researchers in breaststroke Dr Veronique Colman. The breaststroke has the greatest variation in intra-cyclic velocity of the four strokes and has the most variants in style. This chapter is therefore composed of four parts: the phases of a stroke cycle, the intra-cyclic velocity variations, the styles (undulating vs. flat), and the influence of body characteristics.